Gas exchanges in Vitis vinifera under water stress regime. III. Abscisic acid and varietal behavior - de Albuquerque Regina, Murillo; Carbonneau, Alain (Pesquisa Agropecuaria Brasileira, 1997)
The effect of water stress on the regulation of gas exchange and on the accumulation of abscisic acid (ABA) in the leaves of different cultivars of Vitis vinifera L. has been analysed with the purposes of characterizing the varietal behavior and of identifying a marker for the different forms of response. Two-year old plants grafted on 'Fercal', planted in plastic pots and cultivated under controlled conditions were used. Long period of water stress (20 days) revealed two groups of cultivars with different sensitivities at the gas exchange level. The ABA content of the leaves was related to the functioning of the stomata, showing that the most sensitive cultivars presented the lowest contents of ABA in the test plants, whereas the greatest accumulations of this hormone occurred in the stressed plants.